Role of in-service stress and strain fields on the hydrogen embrittlement of the pressure vessel constituent materials in a pressurized water reactor. (December 2017) - Toribio, J.; Vergara, D.; Lorenzo, M.
Abstract: The in-service brittle fracture of a structural component of a nuclear power plant (NPP) is a problem of major concern in engineering. During nuclear energy generation, the wall of the nuclear reactor pressure vessel (RPV) is exposed to a hydrogenating environment leading to a fracture phenomenon known as hydrogen embrittlement (HE). This in-service failure is ruled by hydrogen diffusion from the hydrogenating source (the inner side of the RPV) towards certain places inside the vessel where hydrogen is accumulated and microstructural damage is located. The diffusion process is highly influenced by the stress and plastic strain distributions. For achieving a realistic estimation of the hydrogen accumulation by diffusion, both the in-service thermal stress and the manufacturing induced residual stress and strain (due to tempering heat treatment) must be taken into account. In this paper, a numerical analysis of the hydrogen diffusion assisted by stress and strain is carried out to find out the hydrogen accumulation within the wall of a real pressurized water reactor (PWR) for diverse heat treatment conditions. Results reveal the key role of the in-service thermal stress which enhances the hydrogen diffusion through the constituents' materials of a PWR pressure vessel. Highlights: Residual stress-strain affects the hydrogen embrittlement (HE) of the base material. The resistance to hydrogen embrittlement is improved by adding a cladding layer. HE problems arise in the interface between the base material and the cladding layer. A rise of tempering temperature improves the HE resistance of the vessel material. An increase of tempering time improves the HE resistance of the vessel material. Enlarging the tempering time is better than increasing the tempering temperature.